PENGARUH INFORMASI WEBSITE PERUSAHAAN GO-PUBLIC DALAM PROSES PENGAMBILAN KEPUTUSAN INVESTASI (MINAT INVESTASI) OLEH INVESTOR POTENSIAL DI PONTIANAK - B1031131021, DEWY RISTA FEBRIANTY (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
The purpose of this research was to analyze and determine the factors that effect the interests of accounting students on the Faculty of Economics and Business, University of Tanjungpura to have a career in the public accounting profession. Some of the factors used in this research, which effects the career interests in the public accounting profession are salaries, professional training, working environment, labor market considerations, and professional recognition. The population in this research were the accounting students on the faculty of economics and the sample was accounting students batch of 2013, who have taken the subject of public sector accounting amounted to 100 respondents. Keywords: public accountant, career selection, salaries, professional training, work environment, consideration of the labor market, professional recognition.